The Efficacy of Sexual Intercourse Or Masturbation For The Expulsion Of Distal Ureteral Stones In Men: A Systematic Review And Meta-analysis Of Randomized-controlled Trials - Lu, Yi; Zhang, Wanyu; Su, Hao; Ma, Chengquan; Li, Hongjun (Urology Journal, 2022)
Purpose: Several randomized-controlled trials (RCTs) were performed to compare the efficacy of sexual intercourse or masturbation and no sexual activity in treating distal ureteral stones, indicating conflicting results. The meta-analysis was conducted to assess the role of sexual intercourse or masturbation in the treatment of distal ureteral calculi. Materials and Methods: PubMed, Cochrane Library, EMBASE, Scopus, Clinicaltrail.gov, and Web of Science were searched by October 2021. Men who were instructed of no sexual intercourse or masturbation, and only received standard symptomatic treatment are comparators. Relative risk (RR), weighted mean difference (WMD), and their 95% confidence intervals (CIs) were calculated using random or fixed effects models. Results: Five RCTs including 500 subjects were analyzed in the study. Compared with controls, subjects in experimental group had significantly higher expulsion rate at 2nd and 4th week (95%CI: 1.334 to 2.638, RR: 1.876, I2 = 73.6%, P < .001; 95%CI: 1.148 to 1.752, RR: 1.418, I2 = 55.9%, P < .001), significantly decreased requirement for analgesic injections (95%CI: -1.071 to -.126, WMD: -.598, I2 = 90.3%, P = .013), and significantly shorter expulsion time (95%CI: -6.941 to -.436, WMD: -3.689, I2 = 83.7%, P = .026). Conclusion: Performing sexual intercourse or masturbation 3 or 4 times a week can be an alternative treatment option of distal ureteral calculi (0-10 mm in size). However, more clinical evidence with better designs solving raised concerns is warranted.